The Crustal Stress Field Inferred From Focal Mechanisms in Northern Chile. Issue 8 (26th April 2021) - Herrera, Carlos; Cassidy, John F.; Dosso, Stan E.; Dettmer, Jan; Bloch, Wasja; Sippl, Christian; Salazar, Pablo
Abstract: We ​study the spatial variability of the crustal stress in northern Chile. A margin‐parallel compressive crustal stress regime is inferred along the coastal region between 19° and 23.5°S, similar to stress observations in Cascadia and Japan. The Andean Precordillera shows a distinct stress field associated with a strike‐slip faulting regime around 21°S. These results are constrained by over a decade of observations, for which earthquake catalogs report thousands of events in the continental crust. We present focal mechanisms for 817 of these crustal earthquakes, including mechanism qualities. The best mechanisms were grouped and inverted to infer the stress‐field variability. We interpret the margin‐parallel compression to be caused by the concave shape of the margin and the locking of the plate interface. The inferred strike‐slip regime in the Andes agrees with previous studies and has been proposed to be mostly caused by local stresses imposed by a thicker crust. Plain Language Summary: New observations of thousands of earthquakes occurring within the continental crust (depths <60 km) in northern Chile provide an opportunity to study the tectonic forces acting in this region of the South American continent. We obtain fault orientations and slip directions of 817 crustal earthquakes. The orientations are used to understand the stresses that cause deformation of the crust. With hundreds of earthquakes studied, we can resolve differences in the stress between coastal and inland regions: The coastal region experiences a compression along an approximate north‐south direction. Further east, near the Andes mountains, compression is nearly east‐west, almost parallel to the collision direction of the tectonic plates. This could be mostly due to local stresses acting in higher topography regions. Here, earthquakes occur mostly in nearly vertical faults with slip in the horizontal direction. Conversely, the compression near the coast is likely due to the bending of this region along the coastline, in combination with the locking on the plate interface between the Nazca and South American tectonic plates. The results are remarkably similar to western North America and Japan, where the shape of plate boundaries cause similar stresses. Key Points: We resolve spatial variability of the regional crustal stress field in northern Chile based on focal mechanisms of crustal earthquakes Margin‐parallel compressional crustal stress is observed along the coast and may be due to the concave margin and friction on the interface A strike‐slip regime is observed toward the Andean Precordillera at 21°S, where the elevated topography could affect the local stress